Pimecrolimus for the treatment of atopic dermatitis. Issue 1 (January 2005) - Breuer, Kristine; Werfel, Thomas T; Kapp, Alexander
Atopic dermatitis is a chronic inflammatory skin disease which runs periods of exacerbations and remissions. The calcineurin inhibitor pimecrolimus – an immunomodulatory macrolactam – is a cell-selective inhibitor of inflammatory cytokines specifically developed to treat inflammatory skin diseases. In this article the currently available data on pharmacology, clinical efficacy and safety are reviewed. In several short and long-term studies on children and adults with AD, most patients showed an improvement of their eczema, paralleled by a rapid relief of pruritus. Moreover, pimecrolimus reduced the incidence of flares and the need for corticosteroids in children and adults. Pimecrolimus has a favourable safety profile. In several pharmacokinetic studies, the topical application of pimecrolimus did not lead to significant blood levels in children and adults. Symptoms of irritation such as burning, erythema and pruritus may occur in the first days. A significant increase of skin infections or systemic infections was not observed, though the incidence of viral skin infections tended to increase slightly. Thus, pimecrolimus may represent an alternative compound to the topical corticosteroids for the treatment of atopic dermatitis.